2014
DOI: 10.1260/0263-0923.33.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Passenger Noise and Whole-Body Vibration Exposure—A Comparative Field Study of Commercial Buses

Abstract: The goal of this paper was to evaluate bus passengers' comfort with regard to noise and whole-body vibration. All types of existing buses used in Tehran urban services were considered for study. The measured noise levels in all buses were higher than the recommendations in W.H.O (1999) as well as Iran Department of Environment (2001), while the vibrations at the passenger seats were non uncomfortable vibrations according to ISO 2631-1-1997. In addition, the results demonstrated that the age and type of bus can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Passenger seats, engine, and wheels of a bus are major sources of vibration inside buses [84] Iran, 2014…”
Section: Quality Of Servicementioning
confidence: 99%
“…Passenger seats, engine, and wheels of a bus are major sources of vibration inside buses [84] Iran, 2014…”
Section: Quality Of Servicementioning
confidence: 99%
“…Noise is majorly created by the engine, gear, pedal, accelerator and breaks. (Nassiri, Ebrahimi, Monazzam, Rahimi, & Shalkouhi, 2014;Nadri, et al, 2012). It was also found that the engine and wheels are the major sources of noise inside the buses (Nassiri, Ebrahimi, Monazzam, Rahimi, & Shalkouhi, 2014).…”
Section: Sources Of Noise In Busmentioning
confidence: 99%
“…Vehicle ride comfort is one of the important performance parameters determining the desirability and marketability of an automobile. The ride comfort analysis and prediction is an active research area; there has been considerable work (for example, see the literature 714 ) towards understanding ride comfort in terms of vibration perception, road inputs, dynamic behaviour of vehicle suspension components and also the human body dynamics. The aim has been to develop reliable virtual prototypes so as to reduce reliance of expensive physical prototype trials.…”
Section: Introductionmentioning
confidence: 99%